Reggae Music Community Practice in The City of Bontang (Descriptive Study of Bontang Reggae Community): Praktik Komunitas Musik Reggae di Kota Bontang (Studi Deskriptif Bontang Reggae Community) - Syafa, Muhammad Fachmi; Murlianti, Sri (Progress In Social Development, 2020)
ABSTRACT: This study describes the practice of social life in the field of music in the city of Bontang, based on a sociological perspective using the generative formulation of the theory of Pierre Bourdieu (Habitus x Modal) + Ranah = Practice. This shows that the existence of the Bontang Reggae Community has produced several groups consisting of Reggae Grill, Slow Reggae, and Reggae Vibe groups as actors who practice in the realm of reggae music. This group was formed because of the different knowledge and understanding in the field of reggae music as a realm of space for social life, which then produced various habitus according to the realm of music in each group. Also, the existence of each group has been supported by the existence of a classification of capital which according to Bourdieu consists of four fundamental capitals including material capital, social capital, cultural capital, and symbolic capital. The three groups produce a practice resulting from dialectical relations through habitus-modal interactions in different and prominent domains of reggae music. The Reggae Grill group produces practices that come from symbolic capital, and circular habitus or the use of Cannabis, then the Slow Reggae group produces modern music practices that come from material capital and cultural capital, and the Reggae Vibe group produces solidarity practices that come from cultural capital and capital. symbolic, as well as group habitus. ABSTRAK: Penelitian ini menggambarkan praktik kehidupan sosial masyarakat pada bidang seni musik di kota Bontang, berdasarkan perspektif sosiologi dengan menggunakan rumusan generatif teori Pierre Bourdieu (Habitus x Modal) + Ranah = Praktik. Menunjukkan bahwa keberadaan Bontang Reggae Community telah melahirkan beberapa kelompok yang terdiri dari kelompok Reggae Grill, Slow Reggae, dan Reggae Vibe sebagai aktor yang melakukan praktik dalam ranah kehidupan seni musik reggae. Kelompok ini terbentuk karna adanya pengetahuan dan pemahaman yang berbeda-beda di bidang seni musik reggae sebagai ranah atau ruang kehidupan sosial, yang kemudian menghasilkan berbagai habitus sesuai dengan ranah musik pada masing-masing kelompok. Selain itu, keberadaan setiap kelompok telah didukung dengan adanya klasifikasi modal yang menurut Bourdieu terdiri dari keempat modal fundamental diantaranya adalah, modal material, modal sosial, modal kultural, dan modal simbolik. Ketiga kelompok tersebut menghasilkan sebuah praktik yang dihasilkan dari hubungan dialektis melalui interaksi habitus-modal dalam ranah musik reggae yang berbeda dan menonjol. Kelompok Reggae Grill menghasilkan praktik yang bersumber dari modal simbolik, dan habitus melingkar atau penggunaan Cannabis, kemudian kelompok Slow Reggae menghasilkan praktik musik modern yang bersumber dari modal material dan modal budaya, serta kelompok Reggae Vibe menghasilkan praktik solidaritas yang bersumber dari modal budaya, dan modal simbolik, serta habitus berkelompok.